Performance Analysis of Innovative and Flexible Modern Leadership Towards a Golden Indonesia - Arman; Patasaka, Rini Indryati; Park, Stephen Yong-Seung (Research and Development Agency Ministry of Home Affairs, 2024)
This research aims to understand the role and influence of innovative and flexible modern leadership in pushing Indonesia toward the vision of a golden Indonesia. With research variables, analyzing innovative and flexible modern leadership performance towards a Golden Indonesia involves several important aspects. Three analyses are made regarding this first. Creativity and innovation, second. Collaboration, flexibility, and third. Development of human potential. This involves analyzing leaders’ strategies, policies, and actions to stimulate economic growth, improve governance, and increase societal well-being through innovative and flexible modern leadership performance toward a golden Indonesia. A quantitative research method used a multistage random sampling survey method, which can open up opportunities to gain a deeper understanding of the leadership phenomenon, with 1200 respondents throughout Indonesia who are 17 years old or have been married for two years. The findings of the innovative and flexible modern leadership performance analysis towards a Golden Indonesia involve several important aspects, where the modern leadership performance analysis shows creativity and innovation (38%), collaboration and flexibility (29%), and the development of human potential (27%) And the need for modern leadership can be seen in transformational leadership (36%), situational leadership (30%), and servant leadership (28%), I don’t know 6%. By analyzing the data, performing statistical analysis with reliability testing, using software, and identifying patterns. These three things have advantages and disadvantages in certain work situations and will have an impact on the government in the future toward a bright and certain golden Indonesia.